Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^2+x-6\\ =x^2-2x+3x-6\\ =x\left(x-2\right)+3\left(x-2\right)\\ =\left(x+3\right)\left(x-2\right)\)
Đáp án: B
a: \(=a^2-b^4\)
b: \(=\left(a^2+2a\right)^2-9\)
c: \(=a^2-\left(2a+3\right)^2\)
d: \(=a^4-\left(2a-3\right)^2\)
e: \(=\left(-a^2-2a+3\right)^2\)
g: \(=4a^2-a^4\)
Ta có: \(\left(x^3+8\right)=\left(x+2\right)\left(x^2-2x+4\right)\)
=> \(\left(x^3+8\right):\left(x+2\right)\\ =\left(x+2\right)\left(x^2-2x+4\right):\left(x+2\right)\\ =x^2-2x+4\)
Đáp án: D
\(\left(a^3-b^3\right)+\left(a-b\right)^2=\left(a-b\right)\left(a^2+ab+b^2\right)+\left(a-b\right)^2\)
\(=\left(a-b\right)\left(a^2+ab+b^2-a-b\right)\)
\(\left(x^2+1\right)^2-x^4=\left(x^2-x^2+1\right)\left(x^2+x^2+1\right)=2x^2+1\)
\(y^3+8+y^2-4=\left(y+2\right)\left(y^2-2y+4\right)+\left(y-2\right)\left(y+2\right)\)
\(=\left(y+2\right)\left(y^2-y+2\right)\)
\(64a^3+125b^3+5b\left(16a^2-25b^2\right)=\left(4a+5b\right)\left(16a^2-20ab+25b^2\right)+5b\left(....\right)\)
\(=\left(4a+5b\right)16a^2\)
\(\left(x-a\right)^4-\left(x+a\right)^4=\left(x^2-2ax+a^2\right)^2-\left(x^2+2ax+a^2\right)^2\)
\(=2\left(a^2+x^2\right)-4ax\)
a/ x3 + x2 z + y2 z - xyz + y3
= (x + y)(x2 - xy + y2) + z(x2 - xy + y2)
= (x2 - xy + y2)(x + y + z)
\(\left(a^2+2a+4\right)\left(a-2\right)\\ =\left(a-2\right)\left(a^2+2a+2.2\right)\\ =a^3-8\)
Chọn D
Kết quả của tích (a2+2a+4)(a-2) là
(A) (a+2)3
(B) (a−2)3
(C) a3+8
(D) a3−8